The Implementation of Semantic Mapping Strategy on English Vocabulary Mastery - Faruk, Ahmad; Aturahma, Hani (Darussalam English Journal (DEJ), 2023)
This study discusses the learning strategy used by a teacher in delivering material. The strategy in this study uses a semantic mapping strategy. Semantic mapping is a strategy made by connecting words related to topics using arrow diagrams, graphs, or pictures. This research aims to find out the relationship between semantic mapping and influencing student memory and to describe the implementation of semantic mapping strategy on English vocabulary mastery at the tenth grade of MA Raudhatut Tholabah in the academic year of 2022/2023. The design of this study used a descriptive qualitative method. This research was conducted in the tenth grade of MA Raudhotut Tholabah which consisted of 20 students. This research, observations, and interviews were carried out to obtain data, then carried out the analysis and conclusions, The results of the semantic mapping strategy research state that this strategy is very appropriate for learning students' vocabulary mastery. This strategy is very easy to understand with a visual learning style. So, this research was declared successful because the results obtained by students met the predetermined success criteria. Based on the results it proves that the semantic mapping strategy increases students' vocabulary